Urethral Prolapse in three American Pit Bull dogs and its Surgical Management - Manu Prabh Sharma; Ashwani Kumar; Ankit Kohli; Vandana Sangwan (The Indian Veterinary Journal, 2026)
Three American Pit Bull male dogs were presented with blood spotting from the penile region and a pink/red mass at the tip of the glans penis over a period of 6 months. All were young and had no history of breeding. The condition was diagnosed as urethral prolapse on physical examination. The condition was surgically managed by reduction, resection and urethropexy along with urinary catheter fixation. All the dogs recovered without recurrence or any major complications.